2020
DOI: 10.1093/rheumatology/keaa119
|View full text |Cite
|
Sign up to set email alerts
|

New variant in the IL1RN-gene (DIRA) associated with late-onset, CRMO-like presentation

Abstract: Objective To report a chronic recurrent multifocal osteomyelitis (CRMO)-like clinical phenotype with multisystem inflammation associated with a novel gene variant in the spectrum of IL-1-mediated diseases. Methods A 3-year-old boy presented with recurrent episodes of fever, serositis, pancreatitis and high inflammatory markers with onset at age 13 months. At age 3 years, he started limping. Imaging revealed multifocal pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…In patients with presumed DIRA, a diagnostic workup includes assessing peripheral neutrophilia and elevated inflammatory markers, determining bone involvement (ie, X-ray or bone MRI) and genetic testing 2 120. The differential diagnosis for DIRA includes chronic recurrent multifocal osteomyelitis (CRMO),121 122 synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO)123 syndrome and pustular psoriasis 124. Genetic testing for monogenic defects with overlapping clinical features should include LPIN2, FGR, FBLIM1 for CRMO,125 126 CARD14 for CARD14-mediated psoriasis (CAMPS),127 128 IL36RN for deficiency of IL-36 receptor antagonist,127 128 AP1S3 128 for other pustular psoriasis and MEFV for pyrin-associated autoinflammation with neutrophilic dermatosis 129…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with presumed DIRA, a diagnostic workup includes assessing peripheral neutrophilia and elevated inflammatory markers, determining bone involvement (ie, X-ray or bone MRI) and genetic testing 2 120. The differential diagnosis for DIRA includes chronic recurrent multifocal osteomyelitis (CRMO),121 122 synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO)123 syndrome and pustular psoriasis 124. Genetic testing for monogenic defects with overlapping clinical features should include LPIN2, FGR, FBLIM1 for CRMO,125 126 CARD14 for CARD14-mediated psoriasis (CAMPS),127 128 IL36RN for deficiency of IL-36 receptor antagonist,127 128 AP1S3 128 for other pustular psoriasis and MEFV for pyrin-associated autoinflammation with neutrophilic dermatosis 129…”
Section: Resultsmentioning
confidence: 99%
“…The FDA recently approved both anakinra and rilonacept for treatment of DIRA 53 55. Blocking IL-1α may be necessary to completely block bone inflammation, as observed in a patient who developed osteitis during treatment with canakinumab, which only blocks IL-1β 121. While anakinra has been used initially in all patients with DIRA to achieve disease control, rilonacept can be used to maintain remission 120.…”
Section: Resultsmentioning
confidence: 99%
“…One is Majeed syndrome which is the focus of this review. The other is the deficiency of the interleukin-1 receptor antagonist (DIRA) in which , sterile multifocal osteomyelitis/osteitis and skin pustulosis are the dominant phenotypes [34,35,[67][68][69][70][71][72][73][74][75][76][77][78]. Patients with DIRA present in infancy with systemic inflammation, severe multifocal osteomyelitis and pustulosis of the skin.…”
Section: Autoinflammatory Bone Disease Syndromesmentioning
confidence: 99%
“…Patients with DIRA present in infancy with systemic inflammation, severe multifocal osteomyelitis and pustulosis of the skin. It is caused by either deficiency or loss of function mutations in the gene that encodes the IL-1 receptor antagonist leading to unfettered IL-1 signaling and results in a systemic inflammatory disorder that if left untreated is often fatal [34,35,[67][68][69][70][71][72][73][74][75][76][77][78]. While a direct connection to IL-1 signaling is evident in DIRA, that connection had been less clear in the Majeed syndrome which is caused by pathogenic variants in LPIN2, in which the encoded protein plays a central role in lipid metabolism.…”
Section: Autoinflammatory Bone Disease Syndromesmentioning
confidence: 99%
“…Recently, Kuemmerle-Deschner et al reported the case of an atypical DIRA presentation, CNO-like with a later clinical onset at 1 year of age. This reported case increases the spectrum of DIRA presentation and highlights the importance of considering serum IL-1Ra dosage in patients with early-onset CNO-like bone lesions and biologic inflammation, even without skin manifestations [ 59 ].…”
Section: Monogenic Forms Of Cnomentioning
confidence: 99%